Hydrothermally deposited protective and bioactive coating for magnesium alloys for implant application - Falahieh Asl, Sara Kaabi (2016)
Biocompatible and bioresorbable magnesium and its alloys could be ideal alternatives for currently used implants (Ti, Co–Cr alloys) to overcome their drawbacks of stress shielding and requirement for second surgery when they are used as temporary implants. However, the high corrosion rate of magnesium and its alloys limit their practical application. Thus, in this study, a hydrothermal coating process was developed to provide coatings that may slow the corrosion of magnesium. The hydrothermal process produced a biocompatible and bioresorbable monetite (CaHPO4) coating on AZ31 magnesium substrates. The composition and morphology of coatings were influenced by the deposition temperature. X-ray diffraction (XRD) patterns indicated sharp and well-defined peaks of monetite at low deposition temperature and a mixture of monetite and tricalcium phosphate at higher deposition temperature. Scanning electron microscopy (SEM) study of the morphology showed an increasingly denser coating with higher deposition temperature. Coating adhesion properties were evaluated by a pull-out test indicating cohesive failure at 5.2 to 5.8 MPa stress. It was found that monetite partially converted to hydroxyapatite after 28 days immersion in simulated body fluid (SBF), confirming the bioactivity of the coatings. The hydrothermal deposition method reported here provides crystalline and dense coatings with strong adhesion. It potentially can be a useful process to deposit corrosion protective and biocompatible layers on complex substrate geometries for implant applications.